2014
DOI: 10.1073/pnas.1410443111
|View full text |Cite
|
Sign up to set email alerts
|

Fire responses to postglacial climate change and human impact in northern Patagonia (41–43°S)

Abstract: Forest/steppe boundaries are among the most dynamic ecosystems on Earth and are highly vulnerable to changes in climate and land use. In this study we examine the postglacial history of the Patagonian forest/steppe ecotone (41-43°S) to better understand its sensitivity to past variations in climate, disturbance, and human activity before European colonization. We present regional trends in vegetation and biomass burning, as detected by generalized additive models fitted to seven pollen and charcoal records, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 56 publications
(56 reference statements)
1
41
0
Order By: Relevance
“…Previous analyses of the distribution of GCD sites in climate space showed that the data set has relatively broad coverage with respect to global biomes and climate gradients (Daniau et al, 2012). Many newly published fire-history records exist that can potentially be incorporated into subsequent versions of the GCD (Brown, 2005;Han et al, 2012;Harley et al, 2012;Iglesias et al, 2012;Daniau et al, 2013;Kelly et al, 2013;QuintanaKrupinski et al, 2013;Tan and Huang, 2013;Cordeiro et al, 2014;Courtney Mustaphi and Pisaric, 2014;Dunnette et al, 2014;Higuera et al, 2014;Iglesias and Whitlock, 2014;Neumann et al, 2014;Walsh et al, 2015) and many more are in development that will fill important spatial gaps where fire is key, including Africa and the tropics.…”
Section: Geographical Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analyses of the distribution of GCD sites in climate space showed that the data set has relatively broad coverage with respect to global biomes and climate gradients (Daniau et al, 2012). Many newly published fire-history records exist that can potentially be incorporated into subsequent versions of the GCD (Brown, 2005;Han et al, 2012;Harley et al, 2012;Iglesias et al, 2012;Daniau et al, 2013;Kelly et al, 2013;QuintanaKrupinski et al, 2013;Tan and Huang, 2013;Cordeiro et al, 2014;Courtney Mustaphi and Pisaric, 2014;Dunnette et al, 2014;Higuera et al, 2014;Iglesias and Whitlock, 2014;Neumann et al, 2014;Walsh et al, 2015) and many more are in development that will fill important spatial gaps where fire is key, including Africa and the tropics.…”
Section: Geographical Distributionmentioning
confidence: 99%
“…Sedimentary records are unique among these data sources because of the broad temporal and spatial coverage they provide, which includes reconstructions of fire history at local to global spatial scales and decadal to millennial temporal scales (e.g., Carcaillet et al, 2002;Brown, 2005;Marlon et al, 2008;Iglesias and Whitlock, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…6000-5500 cal yr BP, whereas trees were dominant at ca. 8000-7000 and 6300-6000 cal yr BP (Iglesias et al, 2014). Vegetation fluctuations on centennial time-scales have also been inferred for the early to middle Holocene and associated with periods of erosion at L. Huala Hué (Iglesias et al, 2012a), L. Cóndor (Iglesias et al, 2012b), Cordón Serrucho (Markgraf et al, 2013), L. La Zeta and L. Theobald (Iglesias et al, 2014).…”
mentioning
confidence: 81%
“…Independent proxies at other sites, including diatoms, chironomids and stable isotopes, suggest that the late-glacial/early Holocene transition was characterized by pronounced environmental fluctuations, but the timing of these fluctuations is asynchronous from site to site (Pendall et al, 2001;Huber et al, 2004;Wille et al, 2007;Massaferro et al, 2009;Markgraf and Huber, 2010;Iglesias et al, 2012a). At L. La Zeta (latitude 43ᵒS), for example, a dramatic decline in Nothofagus pollen and rise in Poaceae and Asteraceae occurred between 13,900 and 12,930 cal yr BP (Iglesias et al, 2014). At L.…”
Section: Paleoenvironmental History Of the Eastern Flanks Of The Andesmentioning
confidence: 99%
See 1 more Smart Citation